Mortality in a second gravida following dissecting aortic aneurysm due to Takayasu’s Arteritis - Rawal, S (Journal of Institute of Medicine Nepal, 2007)
Abstract: Takayasu’s arteritis is a vasculitis involving the aorta and its branches. This is a case of undiagnosed Takayasu’s arteritis in a 32 weeks pregnant lady, who presented to the emergency department with complaints of severe chest and epigastric pain and signs consistent with aortic aneurysm. The woman died of aortic dissection two days later. Key words: Pregnancy, Takayasu’s arteritis, aortic aneurysm, dissection